Pengaruh Online Customer Review, Celebrity Endorser, Dan Brand Image Terhadap Keputusan Pembelian Skincare Ms Glow (Studi Kasus Pada Pelanggan Ms Glow Aesthetic Clinic Malang) - Hilda Maulidia Rahma; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis research was conducted to determine the effect of Online Customer Review, CelebrityEndorser, and Brand Image on the Purchase Decision of products skincare Ms Glow to Ms GlowAesthetic Clinic Malang Customers. This research uses explanatory research and quantitativeapproaches. The population and sample of this study are 90 customers of Ms Glow AestheticClinic Malang. In this study informasi collection techniques used in the form of questionnairesand interviews. To solve the problem in this study, using the validity test, reliability test,normality test, multicolinearity test, heteroscedasticity test, multiple linear regression analysistest, F test, t test, and the coefficient of determination test. Research using multiple linearregression analysis with the help of SPSS 25. The results of this study are that the OnlineCustomer Review, Celebrity Endorser, and Brand Image variables influence PurchasingDecisions simultaneously, partially the variabels Online Customer Review affect the PurchaseDecision while the Celebrity Endorser and Brand Image partially does not affect the PurchaseDecision of products skincare Ms Glow to customers of Ms Glow Aesthetic Clinic Malang.Keywords: Online Customer Review, Celebrity Endorser, Brand Image and Purchase Decision